Continuous casting heat transfer model – The spray cooling control problem (Research, Society and Development, 2023)
In the steel industry, the continuous casting process is regarded as the second significant technical innovation after the advent of the oxygen steelmaking process. Prevailing thermal conditions are a dominant factor in the quality of the product. The common practice of spray control in which water flow in the sprays is proportional to the casting speed is inadequate to unsteady state conditions during speed changes. The objectives of the present study were twofold. The first was to study the basic principles of spray control. As a required tool, a mathematical model for the thermal field was developed. This model was to be used to simulate the temperature distribution in the strand. The second objective was to use these principles to develop a model for controlling the sprays. The thermal model has been used to analyze the effects of both practices on the surface temperature of the strand. The results have shown that a significant temperature fluctuation can be generated by proportional control and that the new control model realistically predicts the thermal requirements of the strand during changes in casting speed.